Fully automatic affine registration of planar parametric curves - Mikula, Karol; Urbán, Jozef (Proceedings of the Conference Algoritmy, 2016)
A new, fast and fully automatic algorithm for registration of 2D parametric curves is proposed in this paper. Two functionals, expressing difference between given curves are defined and minimized. The first one is based on difference in signed curvature of curves. Its optimization leads to optimal curve parametrization offset. The second one is based on distances between corresponding points and leads to optimal affine transformation parameters. Optimization of the parametrization offset is necessary in order to identify points correspondence of given curves. Numerical experiments on real data are presented and discussed.